Health Education on the Importance of Physical Activity for Elementary School Children at SD Negeri 101900 Lubuk Pakam - Isidorus Jehaman; Waode Riska Astuti Aini; Redi Tantangan; Raynald Ignasius Ginting (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Physical activity is an essential component that supports the growth, development, physical fitness, and overall health of elementary school children. However, rapid technological advances accompanied by increased use of digital devices have led many children to engage more frequently in sedentary or low-activity behaviors. This condition may negatively affect both physical and psychological health, including reduced physical fitness, an increased risk of overweight and obesity, and decreased learning ability and social interaction. Therefore, educational interventions are needed to improve children's knowledge and awareness of the importance of physical activity from an early age. This educational program aimed to enhance the knowledge and awareness of students at SD Negeri 101900 Lubuk Pakam regarding the benefits of physical activity for health, growth, and development. The intervention employed interactive lectures, demonstrations of simple physical activities, group discussions, and question-and-answer sessions. A total of 30 elementary school students participated in this program. The effectiveness of the intervention was evaluated by measuring participants' knowledge using questionnaires administered before and after the educational session. The results showed an improvement in students' knowledge following the intervention. The mean pre-intervention score increased from 61.3% to 87.7% after the intervention, representing an increase of 26.4 percentage points (43.1%). Furthermore, statistical analysis using the Paired Sample t-Test revealed a significant difference between pre- and post-intervention scores (p = 0.001; p < 0.05). These findings indicate that health education on the importance of physical activity effectively improved elementary school students' knowledge. This program has the potential to serve as a promotive and preventive strategy for fostering active and healthy lifestyle behaviors among school-aged children.